MRI Findings in Rasmussen’s Encephalitis - Mendes Dos Santos, Carolina (2012)
Introduction: Rasmussen’s encephalitis is a chronic inflammatory encephalitis of unknown etiology. Clinical, imaging and electroencephalographic characteristic findings allow its diagnosis. Serial brain MRI evaluation of these patients has a characteristic pattern of temporal evolution. Regarding a clinical case, the authors make a brief review of this pathology, with particular emphasis on the MRI findings. Case Report: Female child, seven years old, who started a drug-resistent focal epilepsy at the age of four. The video-EEG revealed a left fronto-temporal epileptogenic focus. The serial MRI evaluation showed a left fronto-temporal and insular lesion with variation of its imaging features over time. After thorough investigation, the diagnosis of exclusion was that of Rasmussen’s encephalitis. Conclusion: MRI plays an important role in the diagnosis and monitoring of Rasmussen’s encephalitis. Regarding a clinical case, we review this pathology, specially its MRI findings.